Functional transcriptomics of wild-caught Lutzomyia intermedia salivary glands: identification of a protective salivary protein against Leishmania braziliensis infection. - Tatiana R de Moura; Fabiano Oliveira; Marcia W Carneiro; José Carlos Miranda; Jorge Clarêncio; Manoel Barral-Netto; Cláudia Brodskyn; Aldina Barral; José M C Ribeiro; Jesus G Valenzuela; Camila I de Oliveira (Public Library of Science (PLoS), 2013)
BACKGROUND: Leishmania parasites are transmitted in the presence of sand fly saliva. Together with the parasite, the sand fly injects salivary components that change the environment at the feeding site. Mice immunized with Phlebotomus papatasi salivary gland (SG) homogenate are protected against Leishmania major infection, while immunity to Lutzomyia intermedia SG homogenate exacerbated experimental Leishmania braziliensis infection. In humans, antibodies to Lu. intermedia saliva are associated with risk of acquiring L. braziliensis infection. Despite these important findings, there is no information regarding the repertoire of Lu. intermedia salivary proteins. METHODS AND FINDINGS: A cDNA library from the Salivary Glands (SGs) of wild-caught Lu. intermedia was constructed, sequenced, and complemented by a proteomic approach based on 1D SDS PAGE and mass/mass spectrometry to validate the transcripts present in this cDNA library. We identified the most abundant transcripts and proteins reported in other sand fly species as well as novel proteins such as neurotoxin-like proteins, peptides with ML domain, and three small peptides found so far only in this sand fly species. DNA plasmids coding for ten selected transcripts were constructed and used to immunize BALB/c mice to study their immunogenicity. Plasmid Linb-11--coding for a 4.5-kDa protein--induced a cellular immune response and conferred protection against L. braziliensis infection. This protection correlated with a decreased parasite load and an increased frequency of IFN-γ-producing cells. CONCLUSIONS: We identified the most abundant and novel proteins present in the SGs of Lu. intermedia, a vector of cutaneous leishmaniasis in the Americas. We also show for the first time that immunity to a single salivary protein from Lu. intermedia can protect against cutaneous leishmaniasis caused by L. braziliensis.